Inflation rate impact on the share returns of real sector companies in AP Vojvodina - Anđelić, Goran; Penezić, Nenad; Tot, Vilmoš; Milošević, Marko R. (The European Journal of Applied Economics, 2018)
Taking into account the current trends in the domestic financial market, the subject of this research is the analysis, testing and quantification of the inflation rate impact on the daily share returns of the real sector companies in AP Vojvodina. The aim of the research is to generate concrete, practically tested and quantified knowledge about the possibilities and efficiency of the GARCH models application to quantify the inflation rate impact on the share returns of the observed companies. The period covered by the survey is from 2006 to 2016 and it includes the real sector companies of AP Vojvodina whose shares are quoted within the stock exchange index BELEXline. The research results show the exact correlation between the daily return rates of the observed companies and the financial risk factor - the inflation rate. The results also show a positive impact of the variable inflation rate on the returns of companies NIS a.d (0.013876), Sojaprotein a.d (0.019167) and Vital a.d (0.051056), and a negative impact on the returns of the company Veterinary Institute a.d (-0.000183). The research results confirm the role and significance of the application of econometric models in order to quantify financial risk factors of returns from investment activities in the real sector companies of AP Vojvodina.